Safety and Efficacy of Laparoscopic Versus Open Gastrectomy in Patients With Advanced Gastric Cancer Following Neoadjuvant Chemotherapy: A Meta-Analysis - Liao, Xu-Liang; Liang, Xian-Wen; Pang, Hua-Yang; Yang, Kun; Chen, Xin-Zu; Chen, Xiao-Long; Liu, Kai; Zhao, Lin-Yong; Zhang, Wei-Han; Hu, Jian-Kun (Frontiers in Oncology, 2021)
Background Given the expanding clinical applications of laparoscopic surgery and neoadjuvant chemotherapy in advanced gastric cancer treatment, there is an emerging need to summarize the few evidences that evaluated the safety and efficacy of laparoscopic versus open gastrectomy in patients with advanced gastric cancer (AGC) following neoadjuvant chemotherapy (NAC). Methods From January 1 to 2, 2021, we searched Ovid Embase, PubMed, Cochrane central register Trials (Ovid), and web of science to find relevant studies published in English, and two authors independently performed literature screening, quality assessment of the included studies, data extraction, and data analysis. This study was registered with PROSPERO (CRD42021228845). Results The initial search retrieved 1567 articles, and 6 studies were finally included in the meta-analysis review, which comprised 2 randomized control trials and 4 observational studies involving 288 laparoscopic gastrectomy (LG) and 416 open gastrectomy (OG) AGC patients treated with NAC. For intraoperative conditions, R0 resection rate, blood transfusion, intraoperative blood loss, number of lymph nodes dissected, proximal margin, and distal margin were comparable between LG group and open OG group. For postoperative short-term clinical outcomes, LG has significantly less postoperative complications (OR = 0.65, 95%CI: 0.42–1.00, p = 0.05) and shorter postoperative time to first aerofluxus (WMD = -0.57d, 95%CI: -0.89–0.25, p = 0.0004) than OG, and anastomotic leakage, pulmonary infection, pleural effusion, surgical site infection, thrombosis, intestinal obstruction, peritoneal effusion or abscess formation, postoperative time to first defecation, postoperative time to first liquid diet, and postoperative length of stay were comparable between the two groups. For postoperative survival outcomes, there were no significant differences in disease-free survival (DFS) and overall survival (OS) between the two groups. Conclusion The available evidences indicated that LG is an effective and feasible technology for the treatment of AGC patients treated with NAC, and LG patients have much less postoperative complications and faster bowel function recovery than OG patients. Systematic Review Registration PROSPERO database (identifier, CRD42021228845).